Les tensions constitutives du “développement durable” - Fabrice Flipo (Développement Durable et Territoires)
The conceptualization of sustainable development in three pillars is misleading and wrongfully obvious.  With criticism, it appears apolitical, technocratic and enchased in a dated culture and in crisis. Under these conditions, to want to study, develop and reinforce « the social pillar » as an isolated and identified category can be counterproductive compared to objectives of reduction of the inequalities, whatever they are. We are confronted with a crisis of the concepts which govern collective organisation, it is necessary to take note and hold this as a starting point. We try to show that the difficulty, from now on, is not to deepen research in the existing categories but of opening the democratic and interdisciplinary dialogue towards the construction of new categories.